EHBP1L1 Drives Immune Evasion in Renal Cell Carcinoma through Binding and Stabilizing JAK1. Issue 11 (12th February 2023) - Pan, Yihui; Shu, Guannan; Fu, Liangmin; Huang, Kangbo; Zhou, Xinwei; Gui, Chengpeng; Liu, Huashan; Jin, Xiaohan; Chen, Minyu; Li, Pengju; Cen, Junjie; Feng, Zihao; et al.
Abstract: High lymphocyte infiltration and immunosuppression characterize the tumor microenvironment (TME) in renal cell carcinoma (RCC). There is an urgent need to elucidate how tumor cells escape the immune attack and to develop novel therapeutic targets to enhance the efficacy of immune checkpoint blockade (ICB) in RCC. Overactivated IFN‐ γ ‐induced JAK/STAT signaling involves in such TME, but the underlying mechanisms remain elusive. Here, EH domain‐binding protein 1‐like protein 1 (EHBP1L1) is identified as a crucial mediator of IFN‐ γ /JAK1/STAT1/PD‐L1 signaling in RCC. EHBP1L1 is highly expressed in RCC, and high EHBP1L1 expression levels are correlated with poor prognosis and resistance to ICB. EHBP1L1 depletion significantly inhibits tumor growth, which is attributed to enhanced CD8 + T cell‐mediated antitumor immunity. Mechanistically, EHBP1L1 interacts with and stabilizes JAK1. By competing with SOCS1, EHBP1L1 protects JAK1 from proteasomal degradation, which leads to elevated JAK1 protein levels and JAK1/STAT1/PD‐L1 signaling activity, thereby forming an immunosuppressive TME. Furthermore, the combination of EHBP1L1 inhibition and ICB reprograms the immunosuppressive TME and prevents tumor immune evasion, thus significantly reinforcing the therapeutic efficacy of ICB in RCC patient‐derived xenograft (PDX) models. These findings reveal the vital role of EHBP1L1 in immune evasion in RCC, which may be a potential complement for ICB therapy. Abstract : Herein the authors identify EH domain‐binding protein 1‐like protein 1(EHBP1L1) as a key regulator of immune escape in renal cell carcinoma (RCC). EHBP1L1 interacts with and stabilizes Janus kinase 1 (JAK1), thus significantly inhibiting tumor growth and enhancing anti‐tumor immune response. This work reveals a potential therapeutic target for improving the efficacy of cancer immunotherapy in RCC patients.